High-resolution mapping of substantia nigra in Parkinson’s disease using 7 tesla magnetic resonance imaging - Christopher F. Madelung; Annemette Løkkegaard; Søren A. Fuglsang; Marta M. Marques; Vincent O. Boer; Kristoffer H. Madsen; Anne-Mette Hejl; David Meder; Hartwig R. Siebner (npj Parkinson's Disease)
Abstract Parkinson’s disease causes a progressive loss of dopaminergic neurons and iron accumulation in the substantia nigra pars compacta. Using ultra-high field magnetic resonance imaging (MRI) at 7 tesla in 43 Parkinson’s patients and 24 healthy controls, we analyzed the voxel-wise pattern of structural disintegration of dopamine neurons with neuromelanin-sensitive MRI, along with assessing iron accumulation using R2* and quantitative susceptibility mapping (QSM). We also explored correlations between these measures and the severity of residual motor symptoms in the on-medication state and other clinical variables. Differences were most notable in the nigrosomes within the pars compacta, with patients showing reduced neuromelanin signals and increased QSM values. Severity and asymmetry of motor symptoms correlated with higher R2* and QSM values in nigrosome N1. Thus, ultra-high field MRI provides high-resolution maps of various aspects of the underlying neurodegenerative process which reflect individual motor impairment in Parkinson’s disease.